Relationship between Knowledge, Attitude and Behavior of Postnatal Woman Toward Participation in Permanent Contraception - Jhon Heriansyah; Azhari Azhari; Firmansyah Basir; Theodorus Theodorus (Indonesian Society of Obstetrics and Gynecology, 2018)
Objective: To investigate the association between knowledge, attitude, and behavior towards participation in permanent contraception and describe factors that could affect participation of permanent contraception in women in RSMH Palembang. Methods: This case control study was conducted at the Department of Obstetrics and Gynecology, Dr. Mohammad Hoesin Hospital/ Faculty of Medicine, Universitas Sriwijaya, Palembang, during the period of June 2016 to December 2016. Sample of the cases group was woman who agreed to use permanent contraception while control sample was women who refuse to use permanent contraception. Data were collected using a questionnaire. Statistical analysis was performed using SPSS. Results: There was a significant association between attitude, behavior, husband support, and disease complications with participation of permanent contraception. Factors that influenced participation of permanent contraception in woman in RSMH Palembang include husband support and behavior. Conclusion: Factors that influence the participation of women in RSMH safe contraception Palembang include support for her husband and behavior. [Indones J Obstet Gynecol 2018; 6-1: 39-44] Keywords: family planning, participation, permanent contraception